2019
DOI: 10.12928/telkomnika.v17i2.11755
|View full text |Cite
|
Sign up to set email alerts
|

KAFA: A novel interoperability open framework to utilize Indonesian electronic identity card

Abstract: Indonesian people have electronic citizen card called e-KTP. e-KTP is NFC based technology embedded inside Indonesian citizenship identity card. e-KTP technology has never been used until now since it was launch officially by the government. This research proposes an independent framework for bridging the gap between Indonesia regulation for e-KTP and commercial use in the many commercial or organization sector. The Framework proposes interoperability framework using novel combination component, there are e-KT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In the presidential election, it was found that the high use of ID cards and passports to vote was a strengthening of political rights as a form of Indonesia being a state of law and democracy (11); (12). 102/PUU-VII/2009 accommodates the use of ID cards, implications for the availability of ballots during voting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the presidential election, it was found that the high use of ID cards and passports to vote was a strengthening of political rights as a form of Indonesia being a state of law and democracy (11); (12). 102/PUU-VII/2009 accommodates the use of ID cards, implications for the availability of ballots during voting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are three technologies for transferring data from an IoT device. First, it is a fundamental element for pulling and extracting data from objects, second, Near Field Communication (NFC) network technology for exchanging information for short distances, and third, a program for recording the data [17,21,22]. The Secure IoT Data Model is a specification of the different types of data that are collected, streamed, stored, and processed by the SecureIoT platform.…”
Section: Iot Frameworkmentioning
confidence: 99%
“…Identity card (E-KTP) have near field communication (NFC) technology inside it. NFC is a short-range radio technology that allows communication between devices by touching each other or holding adjacent devices [22]. It is a new technology safer than standard RFID [23], E-KTP conforms to ISO 7810 with a format the size of a credit card, namely 53.98 mm x 85.60 mm.…”
Section: Introductionmentioning
confidence: 99%